Analysis of Figurative Language in Selected Taylor Swift’s Lover Album and Its Contribution to English Learning - Nahdawati; Rahmatul Ummu Arifin; Sitti Hawaena; Uswatun Hasanah; Nanda Safitri (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This research aims to analyze the types of figurative language found in selected songs from Taylor Swift’s Lover album and to interpret their meanings, as well as examine how these figurative languages contribute to English learning. The study focuses on three songs, Cruel Summer, The Archer, and Death by a Thousand Cuts, and applies the theories of Siswantoro (2002), Leech (1981), and Krashen (1982).Using a qualitative descriptive method, data were collected through document analysis and open ended questions. The results identified seven types of figurative language: metaphor, symbol, hyperbole, personification, simile, paradox, and synecdoche. Metaphor and symbol were the most frequently used types, followed by hyperbole, personification, simile, paradox, and synecdoche. These figurative expressions conveyed abstract emotional experiences such as heartbreak, longing, vulnerability, and self-reflection. The findings also show that analyzing figurative language through song lyrics supports English learning by providing meaningful input, enriching vocabulary, and fostering interpretative thinking. The use of authentic materials such as songs creates an affective learning environment that aligns with Krashen’s Second Language Acquisition theory, particularly the Input Hypothesis and Affective Filter Hypothesis.In conclusion, integrating figurative language analysis through song offers both linguistic and emotional value, making song lyrics a meaningful and engaging medium in the context of English learning.